2004
DOI: 10.1079/pns2003318
|View full text |Cite
|
Sign up to set email alerts
|

Dietary PUFA and the metabolic syndrome in Indian Asians living in the UK

Abstract: Indian Asians living in the UK have a 50 % higher CHD mortality rate compared with the indigenous Caucasian population, which cannot be attributed to traditional risk factors. Instead, features of the metabolic syndrome, including raised plasma triacylglycerol, reduced HDLcholesterol (HDL-C) and an increased proportion of small dense LDL particles, together with insulin resistance and central obesity, are prevalent among this population. The present review examines evidence to support the hypothesis that an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 85 publications
0
16
1
Order By: Relevance
“…It has been hypothesized that fish or LCω3PUFA intake may be associated with lower risk of MetS [ 27 ]. However, data directly linking fish consumption or LCω3PUFA intake to the risk of MetS are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that fish or LCω3PUFA intake may be associated with lower risk of MetS [ 27 ]. However, data directly linking fish consumption or LCω3PUFA intake to the risk of MetS are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Brady et al [196] examined the evidence to support the hypothesis that this increase in metabolic syndrome may in part be due to a dietary imbalance of poly unsaturated fatty acids (PUFA). The results from their investigation demonstrated that dietary supplementation with long chain n-3 PUFA had no impact on insulin action in those subjects consuming either the moderate-or high-n-6 PUFA diet.…”
Section: ) Angiotensin Modulators: Angiotensin Converting Enzyme (Acmentioning
confidence: 98%
“…This is an obvious reflection of the westernization of Japanese dietary habits, and it has had a negative impact. Dietary intake of fat is related to cardiovascular disease [4,7,8], obesity [9,10] and some cancers [2,3]. Greater emphasis has been placed on the potential health benefit of maintaining good nutritional practices.…”
Section: Introductionmentioning
confidence: 99%